Effect of Goal Setting on Psychological State and Swimming Performance in Competitive Swimming - Aouani, Hajer; Amara, Sofiene (Advances in Social Sciences Research Journal, 2024)
The aim of this study was to study the effect of setting a personal goal to achieve on psychological parameters (cognitive anxiety, somatic anxiety and self-confidence) and on the chronometric performance of 50m butterfly in young swimmers. aged between 12 and 13 years old during the 2019/2020 sports season. The population was divided into three groups, the first group1 (G1) underwent competition preparation without a set goal (method1), the second group2 (G2) was oriented towards a vague goal “Do your best” (method2) , whereas, the third group was asked to respond to a difficult-to-achieve goal according to a goal-setting interval (GBI) (method3). The results indicate that method 1 and method 3 increased the level of cognitive and somatic anxiety in swimmers in these two groups (p < 0.05). Furthermore, the self-confidence score was low in group 1 compared to the other two groups. Our results also show that chronometric performance was improved (p < 0.05) better by method 3 than by method 2, while performance remained unchanged in group 1. The difficult goal setting by IFB improved the chronometric performance, but at the same time increased the values of cognitive and somatic anxiety, for this reason the mental trainers and the technical staff were invited to develop associated mental preparation models to this method of goal setting to help swimmers psychologically.